Influence of radial inflow on pressure drop in horizontal oil wells - Lopes de Souza Ribeiro, Heitor; David Hunt, Julian; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2023)
The present work investigates the influence of radial inflows on pressure profiles and maximum axial flow velocity in the center line of horizontal oil production wells. It aims to help in understanding the dynamics of well-reservoir coupling in the context of the oil industry. The flow is characterized as monophasic, incompressible and turbulent, flowing internally to a horizontal pipe 3 m long and 10 cm in diameter. The fluid enters the duct radially through several holes of 1 cm diameter present in the pipe wall. Numerical modeling is performed using ANSYS FLUENT 15.0 software, with post-processing and data collection through CFD-Post. The results show that the presence of the radial influx results in an increase in the pressure differential along the pipe, due to the restriction to the axial flow through the appearance of a hydrodynamic barrier promoted by the radial influx. It is also noted that the higher the radial flow intensity, the greater the maximum axial flow velocity.